A prospective cohort study on severe pain as a risk factor for long-term sickness absence in blue- and white-collar workers. Issue 8 (11th November 2010) - Andersen, Lars Louis; Mortensen, Ole Steen; Hansen, Jørgen Vinsløv; Burr, Hermann
Abstract : Objective: To estimate the impact of pain in different body regions on future long-term sickness absence (LTSA) among blue- and white-collar workers. Method: Prospective cohort study in a representative sample of 5603 employees (the Danish Work Environment Cohort Study) interviewed in 2000, and followed in 2001–2002 in a national sickness absence register. Cox regression analysis was performed to assess the risk estimates of mutually adjusted severe pain in the neck/shoulder, low back, hand/wrist and knees for onset of LTSA, defined as receiving sickness absence compensation for at least 3 consecutive weeks. Age, gender, body mass index, smoking and diagnosed disease were controlled for. Results: In 2000 the prevalence among blue- and white-collar workers, respectively, of severe pain was 33% and 29% (neck/shoulder), 33% and 25% (low back), 16% and 11% (hand/wrists), and 16% and 12% (knees). During 2001–2002, the prevalence of LTSA among blue- and white-collar workers was 18% and 12%, respectively. Hand/wrist pain (HR 1.49, 95% CI 1.23 to 1.81) and low back pain (HR 1.30, 95% CI 1.11 to 1.53) were significant risk factors among the total cohort. Neck/shoulder pain was a significant risk factor among white-collar workers only (HR 1.35, 95% CI 1.21 to 1.85). Knee pain was not a significant risk factor. Conclusion: While hand/wrist pain and low back pain are general risk factors for LTSA, neck/shoulder pain is a specific risk factor among white-collar workers. This study suggests the potential for preventing future LTSA through interventions to manage or reduce musculoskeletal pain.